DAMPAK PERCERAIAN TERHADAP PERKEMBANGAN PENDIDIKAN ANAK - siti hawa (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2019)
This research is entitled "The Impact of Divorce on the Development of Children's Education in Meue Village." As for the problems in this study, namely how the general description of divorce, and the factors that cause divorce in Meue Village, Trienggadeng District, and the impact of divorce on the development of children's education in Meue Village, Trienggadeng District, in this study the author uses the Library Research method. ) and Fild research (Field research) and according to the topic of this discussion, the Al-Quran and a number of books related to the impact of divorce on the development of children's education, scientific writings and other literature related to the impact of divorce on the development of children's education, the authors use as material in this paper. The impact of divorce in the family has a great influence on the development of children's education, both in terms of the achievements achieved by a child will decrease and related to the psychological state of the child who is disturbed, even in the social life of a child will experience a great influence due to family conflicts.